2023
DOI: 10.1002/jsfa.13150
|View full text |Cite
|
Sign up to set email alerts
|

Investigation the nutritional properties of Auricularia auricula pulp fermented with Lactobacillus strains and their effects on gut microbiota

Hongcai Li,
Pei Tan,
Wenzhi Lei
et al.

Abstract: BACKGROUNDAuricularia auricula is rich in bioactive components, and microbial fermentation can further dramatically increase its content and bioavailability. However, there are few studies on the relationship between fermented A. auricula pulp (FAAP) and gut microbiota. In this study, standard strains Lactobacillus plantarum 21801 and 21805 purchased from the China Center of Industrial Culture Collection were used to ferment A. auricula pulp at a ratio of 2:1, with an inoculum of 5%, a fermentation temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The fermentation process contributes to enhancing the nutritional profile of mushrooms. Li et al (2024) indicated that Auricularia auricula pulp undergoes significant changes during fermentation, including a notable decrease in total sugar content and pH and significant increases in soluble protein, total phenol, and total acid content. Fermentation with probiotics substantially increases polyphenols and organic acids in A. auricula pulp, significantly improving its antioxidant activity (Li et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fermentation process contributes to enhancing the nutritional profile of mushrooms. Li et al (2024) indicated that Auricularia auricula pulp undergoes significant changes during fermentation, including a notable decrease in total sugar content and pH and significant increases in soluble protein, total phenol, and total acid content. Fermentation with probiotics substantially increases polyphenols and organic acids in A. auricula pulp, significantly improving its antioxidant activity (Li et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2024) indicated that Auricularia auricula pulp undergoes significant changes during fermentation, including a notable decrease in total sugar content and pH and significant increases in soluble protein, total phenol, and total acid content. Fermentation with probiotics substantially increases polyphenols and organic acids in A. auricula pulp, significantly improving its antioxidant activity (Li et al, 2024). Ultimately, fermented products exhibit a significant increase in total phenolic contents and antioxidant capacity, contributing to their reduced cholesterol levels during fermentation (Chaiyasut et al, 2018;Saelee et al, 2020;Sirilun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%